2004
DOI: 10.1590/s1413-70542004000100017
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades termofísicas da polpa do cupuaçu com diferentes teores de sólidos

Abstract: Este trabalho foi realizado com o objetivo de determinar as propriedades termofísicas difusividade térmica, calor específico e condutividade térmica da polpa do cupuaçu em três condições de teor de sólidos: integral (12ºBrix), 9ºBrix e com eliminação parcial dos sólidos insolúveis (peneirado). A difusividade térmica foi determinada por meio do aparato de Dickerson (1965); para o calor específico, utilizou-se a metodologia do calorímetro de mistura, e a condutividade térmica foi determinada considerando-se a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
6
0
3
Order By: Relevance
“…The values obtained by Araújo et al (2004) for specific experimental heats of cupuassu pulp with a 9 °Brix and sieved, were 3.24 kJ/kg °C, 3,71 kJ/kg °C and 3.18 kJ/kg °C, respectively, close to the pequi pulps with different contents of total soluble solids and at elevated temperatures (40 and 50 °C). Bon et al (2010) found that the specific heat of mango pulp at temperatures of 20, 40, 60 and 80 °C and moisture content between 50 and 90% was between 2.738 to 4.093 kJ/kg °C; where the values of the specific heat of pequi pulp with moisture content of 55% (12 ºBrix) to 70% (6 ºBrix) were within this rating (2.20 to 3.45 kJ/kg °C).…”
Section: Specific Heatmentioning
confidence: 51%
See 2 more Smart Citations
“…The values obtained by Araújo et al (2004) for specific experimental heats of cupuassu pulp with a 9 °Brix and sieved, were 3.24 kJ/kg °C, 3,71 kJ/kg °C and 3.18 kJ/kg °C, respectively, close to the pequi pulps with different contents of total soluble solids and at elevated temperatures (40 and 50 °C). Bon et al (2010) found that the specific heat of mango pulp at temperatures of 20, 40, 60 and 80 °C and moisture content between 50 and 90% was between 2.738 to 4.093 kJ/kg °C; where the values of the specific heat of pequi pulp with moisture content of 55% (12 ºBrix) to 70% (6 ºBrix) were within this rating (2.20 to 3.45 kJ/kg °C).…”
Section: Specific Heatmentioning
confidence: 51%
“…It was observed that the minimum specific heat was 2.20 kJ/kg °C and the maximum specific heat of 3.45 kJ/kg ºC. The specific heat of fruit pulp can vary according to their chemical and physico-chemical composition, in addition to direct influence on determination of the amount of energy being added or removed in process of heating and cooling (ARAÚJO et al, 2004). To Souza et al (2011), the higher the moisture content of the pulp will be higher specific heat, but the effect of the total solids is less important due to the various components (fat, protein, sugars and ash) exert a smaller influence as compared with water.…”
Section: Specific Heatmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Dessa forma, elevados índices de SST estão relacionados com melhor sabor e maior rendimento do fruto em preparações. 25,47 A acidez total titulável (ATT), descrita no presente estudo (0,40%), foi inferior ao 0,71% encontrado por Souza, 25 segundo o qual a ATT é utilizada para classificação de frutos em relação ao sabor, e seu alto teor pode reduzir a aceitação do jenipapo em sua forma in natura. A acidez total titulável pode apresentar acréscimo progressivo em jenipapos armazenados sob condições ambientais durante 28 dias.…”
unclassified
“…46 A ATT maior nos jenipapos maduros pode ser considerada uma característica própria do jenipapo, uma vez que na maioria dos frutos a ATT diminui com a progressão do amadurecimento. 47 Da mesma forma que a composição centesimal (umidade, proteínas, cinzas, lipídios, carboidratos "disponíveis" e fibras alimentares), os compostos bioativos (vitamina C, compostos fenólicos e carotenoides) e os parâmetros físico-químicos (pH, acidez, sólidos solúveis e capacidade antioxidante) também admitiram alterações quando comparados com outros estudos. Basicamente, tais variações ocorreram devido, provavelmente, à variação de época de colheita do jenipapo, estação chuvosa, qualidade e composição do solo, sazonalidade, condições edafoclimáticas e distintas metodologias de análise.…”
unclassified